AN ANALYSIS OF VERBAL AND NON-VERBAL COMMUNICATION IN AUTISTIC CHILDREN - Weny Anita Febriantini; Rahima Fitriati; Lulud Oktaviani (Universitas Teknokrat Indonesia, 2021)
Autism is a developmental disorder characterized by difficulties with social interaction and communication, and by restricted and repetitive behavior. Autistic is a person affected by autism. The level of autism of each individual is varied. It can range from mild to severe. Due to this condition, the person shares some symptoms of the difficulties with social interaction. To make them involved in social interaction, it needs special effort to make them be able to speech or communicate first. For this reason, there should be the use of the combination between verbal and non-verbal communication. Thus, this study attempted to investigate the process of using both kinds of communication in teaching children with autism since children are easier to be threated than adults. To make the distinct result, the participants were from different level of autism. Then, based on the observation and interview, the findings showed that the verbal and non-verbal communication used by the therapist in teaching the autistic children can enhance their social interaction and communication skills.